Discovery of selective platelet-derived growth factor receptor-beta (PDGFR-β) bifunctional small-molecule degraders. (1st January 2023) - Si, Ru; Liu, Nanxin; Wang, Jin; Zhang, Qingqing; Li, Yanchen; Pan, Xiaoyan; Zhang, Jie
Graphical abstract: A series of novel PROTACs targeting membrane proteins were developed, which could selectively degrade PDGFR-β protein in cancer cells. Highlights: Three novel PROTACs were developed based on various E3 ubiquitin ligase ligands and multi-target RTK inhibitor. These PROTACs were able to selectively degrade PDGFR-β protein in a dose-dependent manner. The potency of PROTACs as a PDGFR-β degrader is dependent on binding to POI and E3 ubiquitin ligase. These PROTACs showed no toxicity in normal cells. Abstract: Proteolysis-targeting chimeras (PROTACs) is a promising strategy for treatment of various diseases by degrading of disease-related proteins in recent years. Up to now, most PROTAC molecules are mainly aimed at the degradation of intracellular proteins, but many disease-related proteins are membrane or extracellular proteins. The targeted degradation of membrane proteins would be an attractive and general strategy for discovery of novel PROTACs. Herein, we report the development of multi-targeted kinase inhibitor sorafenib-based PROTACs, they can selectively degrade platelet-derived growth factor receptor beta (PDGFR-β). We provide a method that can be used to degrade cell membrane proteins. To our knowledge, this study also is the first report of PROTAC induced PDGFR-β degradation in cancer cells.